Influence of dispersion state of initial AlN powder on the hydrolysis process in air environment; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Ditts A. A. Aleksander Andreevich; Revva I. B. Inna Borisovna; Grishko N. Y.; Tarnovskiy R. V. (2016, 2016)
Title screen